Prevalence of allergic rhinitis in school going children in Kashmir - Sheikh, Shahnaz; Bajaj, Anushree; Dar, Farooq Ahmad; Ahmad, Rauf; Dar, Showkat Ahmad (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2018)
Background: Allergic rhinitis is a common chronic paediatric disorder affecting about 40% of children affected. Allergic rhinitis results in day time fatigue, impairment of cognition and memory which significantly affect the learning process and impact on the school performance of children. The aim of the study was to determine the prevalence of allergic rhinitis in school going children in Kashmir. Methods: Cross sectional questionnaire based observational study. Study group included the school going children chosen randomly from various schools of urban and rural areas of Kashmir valley aged 6-18 years. Results: Out of the 402 children prevalence of allergic rhinitis was 28.85%. Prevalance in urban and rural area school going children was 55.2% and 44.8% respectively. The most common symptom was nasal obstruction 79.31%. The most common allergen was dust mite 77.58% and the most common comorbidity was asthma. Conclusions: The prevalence of allergic rhinitis shows a significant rise in last few years, more common in rural areas, and existing as co-morbidity in a significant proportion of children demanding a comprehensive strategic approach to deal with them.